Innovative Approaches To Enhance Gastric Retention Of Rabeprazole Using Macrocystis Pyrifera Extract (Applied Biological Research, 2023)
The work aimed to formulate and assess floating tablets of Rabeprazole (RBZ)  for treating peptic ulcers. Effervescent tablets were produced (F1-F9) with  variations in the concentration of synthetic polymer HPMC K15 for F1, F2,  and F3; natural polymer Macrocystis pyrifera extract (sodium alginate) for F4,  F5, and F6; and combinations of these polymers for F7, F8, and F9. The  research involved several stages, including pre-formulation studies of the pure  drug. The tablets were assessed for compatibility, pre-formulation, and post formulation studies. The compatibility study indicated that there were no  interfaces between drug and polymers. The floating tablets passed all the pre and post-compression constraints. Among them, F6 exhibited a drug content  of 99.67 ± 0.11% and sustained drug release over 8 h. All formulations  displayed favorable floating behaviour and remained afloat for more than 24  The study concludes that a combination of synthetic (HPMC K15) and  natural (Macrocystis pyrifera extract) polymers found to extend the RBZ  residence time in the stomach and achieve sustained drug discharge. This  approach could hold promise for improving the treatment of peptic ulcers.
Keywords: Effervescent; floating; RBZ; sustained release; tablets; ulcer